ASSESSMENT OF THE QUALITY AND SAFETY OF APPLE CONCENTRATE USED IN FOOD PRODUCTION, AND PROSPECTS FOR ITS FUNCTIONAL APPLICATION - Majidov Kakhramon Khalimovich,; Hakimova Nodira Khayrullaevna,; Dushanova Nilufar Abdukarimovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This study presents the results of a comprehensive assessment of the quality of apple concentrate produced by SP LLC “Afrosiyab-Meva,” compared with international AIJN standards and technical regulations TR TS 021/2011 and 023/2011. Organoleptic, chemical-analytical, microbiological, and toxicological indicators were analyzed to determine the suitability of the concentrate for use in infant food and export. Additionally, the prospects of enriching apple juice with Rosa canina (rosehip) and Mentha piperita (peppermint) extracts to enhance the functional properties of the product were considered.